A proof of concept for cooperation from the quinone groups adjacent to N sites during the metal-free oxidation of glycerol by nitrogen-rich graphene oxide. (22nd October 2021) - Dogra, Ashima; Sharma, Vinit; Barlocco, Ilaria; Villa, Alberto; Gupta, Neeraj
Abstract : A catalytic active site already present in an organic molecule was chemically tagged on the GO surface to prove the role of quinone groups adjacent to N sites in nitrogen-rich carbon materials for the metal-free oxidation of glycerol. Abstract : Glycerol is a key by-product in biodiesel production and can be utilized in the synthesis of value-added chemicals. The low cost and fairly abundant availability of glycerol can be advantageous in producing a variety of pharmaceuticals and cosmetic products. Among the various catalytic transformations, selective oxidation is a promising pathway for the valorization of glycerol. In this present report, we deliver a first proof of concept for the involvement of quinone groups adjacent to N sites on the GO surface, for the selective oxidation of glycerol to dihydroxyacetone (DHA). Graphene oxide is covalently functionalized with 2, 4-dihydroxypyridine (DHP), which resembles the identified active sites in the carbon clusters. As anticipated, the DHP-functionalized graphene oxide catalyst (DHP@GO) improved the conversion of glycerol to DHA, the main product, along with minor amounts of glyceric acid (GA) and fumaric acid (FA).